Health and growth - Spence, Michael, 1943-; Lewis, Maureen A., 1952- (World Bank e-Library., 2009)
This book containes a series of "state of the art" essays on topics related to health and growth. The Commission on Growth and Development (CGD)--in preparing its own Growth Report--wished to take stock of the current state of knowledge and understanding of economic growth, and thus commissioned a series of essays on a range of thematic areas. One such area is health. The following questions are discussed in the book:Does investing in health raise economic growth? Can governments achieve rapid growth or high incomes without investing in health? What are the options and benefits of different an.